Strategies, challenges and opportunities in the rehabilitation of collective housing neighborhoods built between 1940 and 1980 in Spain (Ciudades, 2017)
At the beginning of this century, the cities of our country face a challenge that, in quantitative terms, goes beyond the action referred to the rehabilitation of historic centres and XIX century extensions. This challenge is the rehabilitation of a specific fabric of our cities: neighbourhoods built in the period of 1940-1980, which are undergoing processes of serious urban degradation and can be identified as vulnerable urban areas.This article discusses the strategies taken from the various government levels in urban rehabilitation, and the experiences initiated with the aim of detecting what are the main barriers of all kind (legal, social, economic, cultural) that prevent the systematic practice of these initiatives, which today still have an experimental and minority character, and to forward proposals for action to achieve comprehensive and systematic urban rehabilitation in these neighbourhoods.
Keywords: urban rehabilitation; social housing; public policies; sustainability